2022
DOI: 10.1002/jctb.7164
|View full text |Cite
|
Sign up to set email alerts
|

Microalga‐ and yeast‐based astaxanthin production via nutrient recovery from wastewater for aquaculture practice: an emerging technology for sustainable development

Abstract: Microbial astaxanthin, which is a high‐value antioxidative pigment, has been widely used in aquaculture for pigmentation, immunity enhancement and disease resistance. This novel model is regarded as an emerging way to alleviate environmental pollution and ecological problems. Therefore, cultivation of astaxanthin‐rich microorganisms for aquaculture merits attention of researchers and technicians. This paper presents research progresses in microbial strain screening, astaxanthin formation pathways and inducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 101 publications
(257 reference statements)
1
12
0
Order By: Relevance
“…Secondly, astaxanthin formation is accompanied with the encystment induced under the high ratio of C/N ( Kakizono et al, 1992 ; Li et al, 2022 ). Traditionally, to grow microalgae for astaxanthin production, low concentration of nitrate, ammonia, or organic nitrogen was added in artificial medium ( Lu and Lu, 2022 ). As shown in Table 3 , however, many FPEs, such as soybean processing effluent and meat processing effluent, contain high concentration of TN.…”
Section: Microalgae-based Nutrient Recovery In Food Processing Effluentmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, astaxanthin formation is accompanied with the encystment induced under the high ratio of C/N ( Kakizono et al, 1992 ; Li et al, 2022 ). Traditionally, to grow microalgae for astaxanthin production, low concentration of nitrate, ammonia, or organic nitrogen was added in artificial medium ( Lu and Lu, 2022 ). As shown in Table 3 , however, many FPEs, such as soybean processing effluent and meat processing effluent, contain high concentration of TN.…”
Section: Microalgae-based Nutrient Recovery In Food Processing Effluentmentioning
confidence: 99%
“…In a real-world application, however, high cost of natural astaxanthin production by microalgae cultivation has not been fully addressed. In the market, high sale price (US $2,000–2,500 per kilogram) of natural astaxanthin is hindering the wide application of this valuable bio-product in modern agriculture ( Liu et al, 2013 ; Lu and Lu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have revealed that under high salt stress conditions, the fatty acids in membrane lipids become unsaturated, resulting in an increase in the proportion of unsaturated fatty acids and a decrease in that of saturated fatty acids (Atikij et al, 2019). Not only lipid but also carotenoid content increased under salinity stress, especially MgCl2, and NaCl (Kobayashi et al, 1997;Rad et al, 2011;Pourkarimi et al, 2020;Lu and Lu, 2022).…”
Section: Introductionmentioning
confidence: 96%
“…Firstly, microalgae could remove/reduce nutrients, organic pollutants, heavy metals, chemical oxygen demand (COD), and biological oxygen demand (BOD) in wastewater effectively ( Song et al, 2022 ). Secondly, algal biomass cultivated in wastewater could be used as a potential source of precious products that could be utilized in biofuels, cosmetics, pharmaceuticals, and nutraceuticals fields ( Li et al, 2021 ; Lu and Lu, 2022 ; Lu and Xiao, 2022 ). Thirdly, the microalgae-driven wastewater treatment could help to realize the integration of wastewater treatment, industrial CO 2 sequestration and microalgal biomass valorization, and shift wastewater treatment from linear economy to circular economy ( Vaz et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%